Relationship between EMG Activity and Endurance Time in the Biceps Brachii Muscle during Isokinetic Contraction - Ahamed, Nizam Uddin; Rahman, Matiur; Alqahtani, Mahdi; Altwijri, Omar; Sundaraj, Kenneth; Ahmed, Nasim (2015)
Studies of the surface Electromyographic or EMG signal on the skeleton muscles have provided valuable information on the physiology to understand the motor unit activity strategy during contraction. This paper investigated the relationship between EMG and time during isokinetic contraction (one kind of exercises or movement to increase muscular strength) from the upper limb’s biceps brachii (BB) muscle. Five right hand dominated male subjects (age 23.2±1.6 years) participated in the study. The muscle activation during load lifting (using a standard 6-kg dumbbell) was determined as the root mean square (RMS) Electromyographic signal normalized to the peak RMS EMG signal of a maximal contraction for 10 sec. For the statistical analysis, the slope of the regression relationship was used to test the relationships between EMG and time from the maximal voluntary isokinetic contraction (MVC). The endurance time (10 sec) was divided into 4 phases for analyzing the relationship. The results of the study showed a linear but poor relationship between EMG and time during such contraction, where r2 = 0.11 and F = 3.74. Also, no significant differences exits from the analysis where, P=0.062 (P>0.05). The results provide insights towards applications of biomedical engineering methods in the analysis and control of the neuromuscular system, ergonomics field of research, rehabilitation engineering and movement biomechanics during such type of dynamic contraction.